2015
DOI: 10.1038/pr.2015.231
|View full text |Cite
|
Sign up to set email alerts
|

New developments in cerebral blood flow autoregulation analysis in preterm infants: a mechanistic approach

Abstract: Background: Impaired autoregulation capacity implies that changes in cerebral perfusion follow changes in blood pressure; however, no analytical method has explored such a signal causality relationship in infants. We sought to develop a method to assess cerebral autoregulation from a mechanistic point of view and explored the predictive capacity of the method to classify infants at risk for adverse outcomes. Methods: The partial directed coherence (PDC) method, which considers synchronicity and directionality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
1
15
0
2
Order By: Relevance
“…Being born extremely preterm carries a 20% risk of death, and 25% of survivors have moderate‐to‐severe neurodevelopmental impairment, namely cerebral palsy (CP) or cognitive impairment . The respiratory and circulatory systems of extremely preterm infants are immature, and cerebral autoregulation is impaired, especially during the transition from intrauterine to extrauterine life . In addition, oxygen transport may be impaired by low haemoglobin levels and this makes the developing premature brain susceptible to fluctuations in cerebral blood flow .…”
Section: Introductionmentioning
confidence: 99%
“…Being born extremely preterm carries a 20% risk of death, and 25% of survivors have moderate‐to‐severe neurodevelopmental impairment, namely cerebral palsy (CP) or cognitive impairment . The respiratory and circulatory systems of extremely preterm infants are immature, and cerebral autoregulation is impaired, especially during the transition from intrauterine to extrauterine life . In addition, oxygen transport may be impaired by low haemoglobin levels and this makes the developing premature brain susceptible to fluctuations in cerebral blood flow .…”
Section: Introductionmentioning
confidence: 99%
“…13 In addition, impaired autoregulation is correlated with adverse outcome in infants. 14,15 In 1979, Bada et al first reported that cerebral Doppler studies played a role in the diagnosis of neonatal intracranial injury. 16,17 Doppler provides a valuable tool to follow changes in flow velocities, to assess changes in cerebrovascular resistance and to determine the lower limits of cerebral blood flow autoregulation.…”
Section: Introductionmentioning
confidence: 99%
“…The upper and lower limit of autoregulation are depicted, above and below which the brain is more susceptible to injury. The critical closing pressure (CrCP) is the arterial blood pressure at which the cerebral blood flow is zero.gula tion was associated with increased mortality in this atrisk population28,29)…”
mentioning
confidence: 99%